Qatar steps up to Global Health security: a reflection on the joint external evaluation, 2016 - Mohamed Osman Bala; Mohamad Abdelhalim Chehab; Nagah Abdel Aziz Selim (BMC, 2017)
Abstract Since the commencement of the International Health Regulations in 2007, global public health security has been faced with numerous emerging and ongoing events. Moreover, the Joint External Evaluation is a voluntary tool developed in compliance with the Global Health Security Agenda that represents the high responsibility of international health community towards the increased incidence of emerging and re-emerging diseases. Against this background, between 29th May and 2nd June 2016, a team of World Health Organization consultants arrived to the State of Qatar to assess, in collaboration with national experts, the country's capacity to prevent, detect, and rapidly respond to threats of public health aspect. They identified areas of strength, weakness, and recommendations for improving national health security of Qatar in anticipation of the 2022 FIFA World Cup event. Qatar has demonstrated a leading role in the region through its commitment to International Health Regulations (2005) and population health. Similarly, the Qatar was the first Arab state and seventh volunteering country globally to undergo the Joint External evaluation process. In this review, we highlighted Qatar's achievements and shortcomings of International Health Regulations' core capacities to inform healthcare professionals and the scientific community about the country's contribution toward global health security.